Pengaruh Kemudahan Penggunaan Dan Manfaat Terhadap Penggunaan Aplikasi Pertamina Go Di Kota Semarang (Survey Pada Pengguna Apllikasi Pertamina Go Di Kota Semarang) - Very Torganda Tampubolon; Bulan Prabawani (Universitas Diponegoro, 2018)
Pertamina Go is an online application or tool for customers to conduct digital activities related to Pertamina's products and services. Overall, the main benefits of Pertamina GO is to provide benefits for customers to get information related to Pertamina's services and products. Until february 2017 the number of users only reached 18,284 is still far from the company's target of 100,000 users. This study aims to find out how the effect given by the ease of use and benefits to the use of pertamina go applications in the city of Semarang. The type of research used is explanatory research where data collection techniques used by using the questionnaire tool, the sample used amounted to 100 people by using the accidental technique. The selected respondents were Pertamina Go users in Semarang City. The methodology used to analyze the primary data in this research is the validity test, reliability test, coefficient, coefficient of determination, simple linear regression, multiple linear regression, and significance test (t and F test) with SPSS 16.0. The results showed that ease of use significantly affect the use of Pertamina Go application for 75.7% while the rest is influenced by factors other than ease of use. Perceived of use significantly affect the use of Pertamina Go applications by 77.8% while the rest is explained by factors other than perceieved of use. Meanwhile, simultaneous ease of use and Perceievd of usefulness significant effect on the use of pertamina go equal to 84,4% while the rest influenced by other factors besides ease of use, and perceived of usefulness. This means the better ease of use and benefits the higher the use of Pertamina Go applications In addition the benefits have the greatest influence with the value of regression coefficient of 0.418. Based on the results of the study, researchers suggested that PT. Pertamina (Persero) provides ease of use of the better and improve the existing features contained in the application so that in accordance with the benefits provided in Pertamina Go applications.